Transformasi Digital dalam Manajemen SDM: Studi tentang Strategi Adaptasi di Era AI pada Industri Perbankan Indonesia - Umboh, Willem Engel Oktavianus (LPPM Institut Pendidikan Nusantara Global, 2025)
Digital transformation is fundamentally reshaping Human Resource Management (HRM) in Indonesia’s banking sector, driving strategic evolution alongside the integration of artificial intelligence (AI). This study employs a qualitative descriptive approach to examine how digital tools, particularly AI-powered people analytics, automated recruitment systems, and adaptive e-learning platforms, are redefining traditional HR functions. HR roles are shifting from administrative tasks to strategic, data-driven partnerships that support organizational decision-making and innovation. Findings indicate that AI adoption significantly enhances operational efficiency by streamlining routine processes, improving talent placement accuracy, and enabling predictive analytics for turnover management. These technologies also promote more objective performance evaluations and support personalized employee development, thereby boosting workforce competency and engagement. However, technology adoption alone is insufficient. Successful digital transformation requires a synergistic approach that integrates advanced technologies with an adaptive organizational culture, committed leadership, and comprehensive upskilling and reskilling programs. Compliance with regulations set by the Financial Services Authority (OJK), particularly in data security and cyber resilience, is identified as a critical pillar for sustainable implementation. The study concludes that banks aligning HR strategies with digital capabilities, while fostering a supportive culture and maintaining regulatory compliance, are best positioned to achieve a sustainable competitive advantage in the Society 5.0 era. This research offers practical insights for HR professionals and banking executives to navigate digital transformation, emphasizing the importance of a holistic strategy that balances innovation with human-centric development and robust governance.